Media market concentration, advertising levels, and ad prices - Simon P. Anderson; Oystein Foros; Hans Jarle Kind; Martin Peitz (Center for Economic Studies and ifo Institute (CESifo), 2011)
Standard media economics models imply that increased platform competition decreases ad levels and that mergers reduce per-viewer ad prices. The empirical evidence, however, is mixed. We attribute the theoretical predictions to the combined assumptions that there is no advertising congestion and that viewers single-home. Allowing for crowding in viewer attention spans for ads may reverse standard results, as does allowing viewers to multi-home.
Keywords: D11; D43; L13; 330; media economics; pricing ads; advertising clutter; information congestion; mergers; entry; Medienwirtschaft; Wirtschaftskonzentration; Bottleneck; Werbung; Betriebliche Preispolitik; Medienökonomik; Theorie